Treated domestic effluent as a source of water and nutrients in the hydroponic cultivation of ornamental sunflower - Karoline Santos Gonçalves; Rogério Novaes de Souza; Hans Raj Gheyi; Vital Pedro da Silva Paz; André Dias de Azevedo Neto; Tales Miler Soares (Dyna, 2020)
The use of treated domestic effluent in agriculture is important not only as a source of water but also as a source of nutrients for crops. In this context, the objective of this study was to evaluate its use for the production of ornamental sunflower cv. ‘Anão de Jardim’ in a bench-type low cost hydroponic system, inferring on its technical feasibility and observing the possible impacts on the crop. The experiment was carried out in a greenhouse adopting a completely randomized design with four treatments (T1 - nutrient solution of Furlani 100%, prepared in municipal supply water - control), T2, T3 and T4 - nutrient solution of Furlani, respectively, with 100, 75 and 50% strength, prepared in treated domestic effluent and six replicates, totalizing 24 experimental units, each consisting of 15 plants. All treatments met the nutritional requirements of the plants and presented adequate contents of N, P, K, Ca and Mg in leaf and stem at harvest leading to satisfactory plant growth and produced acceptable commercial grade chapters and stems. The plants under treatment T4 although produced chapters of commercial quality but exhibited great variability in comparison to the other treatments, therefore except this treatment any other treatment can be used for hydroponic production of ornamental sunflower utilizing treated domestic effluents.